(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The fifth instar nymph is described of Livilla retamae (Puton) and L. spectabilis (Flor) and notes are also reported on their geographical distribution, host plants and life-cycle. The first of the two species has a South Mediterranean distribution and lives on plants of the genus Retama Boissier; the second one, monophagous on Spartium junceum L., is diffused in South-Central-Western Europe and the Balcans. In Sicily, both species have a monovoltine cycle, characterized by a relevant adult longevity. Adults emerge in spring (April-May in L. spectabilis; May-June in L. retamae) but oviposit in autumn and during part of the following winter.